A single-center, open-label trial on convenience and complications of rechargeable implantable pulse generators for spinal cord stimulation: the recharge pain trial - Hajiabadi, Mohammad Mehdi; Vicheva, Petya; Unterberg, Andreas; Ahmadi, Rezvan; Jakobs, Martin (Neurosurgical review, 2023)
Rechargeable implantable pulse generators (r-IPGs) have been available for spinal cord stimulation (SCS) claiming to offer a longer service life but demanding continuous monitoring and regular recharging by the patients. The aim of the study (DRKS00021281; Apr 7th, 2020) was to assess the convenience, safety, and acceptance of r-IPGs and their effect on patient lives under long-term therapy.